Systematic bacteriophage selection for the lysis of multiple Pseudomonas aeruginosa strains - Rieper, Finja; Wittmann, Johannes; Bunk, Boyke; Spröer, Cathrin; Häfner, Melanie; Willy, Christian; Müsken, Mathias; Ziehr, Holger; Korf, Imke H.E.; Jahn, Dieter (Frontiers in Cellular and Infection Microbiology, 2025)
Pseudomonas aeruginosa is an opportunistic pathogen causing severe infections of the lung, burn wounds and eyes. Due to its intrinsic high antibiotic resistance the bacterium is difficult to eradicate. A promising therapeutic option is the use of P. aeruginosa-specific bacteriophages. Thus, the implementation of a phage therapy requires their selection, production and systematic administration using multiple strains of the bacterial target. Here, we used 25 phages and tested their susceptibility on 141 different P. aeruginosa strains isolated from patients with different types of infection. Comparative host spectrum analyses were carried out using double agar overlay plaque assay (DPA) and planktonic killing assay (PKA), which resulted in 70% of the cases in the same host range. All phages were assigned to known phage genera, but some of the phages are new species. Isolated members of the genera Pakpunavirus, Pbunavirus (myoviruses), Pawinskivirus, Elvirus (myoviruses, jumbo phages), Litunavirus and Bruynoghevirus (podoviruses) demonstrated great therapeutic potential due to strong lysis behavior on diverse strains. Seven phages were excluded for therapeutic purposes due to genetic determinants that confer lysogenicity. Due to automation with lower time expenditure in execution and analysis, PKA has the higher potential for implementation in diagnostics. Finally, different combinations of phages were tested in silico with various P. aeruginosa strains. Highly efficient phage combinations eradicating multiple P. aeruginosa strains were found. Thus, a solid basis for the development of a broad host range phage therapy was laid.